Molecular cloning and functional characterization of the promoter of a novel Aspergillus flavus inducible gene (AhOMT1) from peanut - Zhuang, Yuhui; Sharif, Yasir; Zeng, Xiaohong; Chen, Suzheng; Chen, Hua; Zhuang, Chunhong; Deng, Ye; Ruan, Miaohong; Chen, Shuanglong; Weijian, Zhuang (Frontiers in Plant Science, 2023)
Peanut is an important oil and food legume crop grown in more than one hundred countries, but the yield and quality are often impaired by different pathogens and diseases, especially aflatoxins jeopardizing human health and causing global concerns. For better management of aflatoxin contamination, we report the cloning and characterization of a novel A. flavus inducible promoter of the O-methyltransferase gene (AhOMT1) from peanut. The AhOMT1 gene was identified as the highest inducible gene by A. flavus infection through genome-wide microarray analysis and verified by qRT-PCR analysis. AhOMT1 gene was studied in detail, and its promoter, fussed with the GUS gene, was introduced into Arabidopsis to generate homozygous transgenic lines. Expression of GUS gene was studied in transgenic plants under the infection of A. flavus. The analysis of AhOMT1 gene characterized by in silico assay, RNAseq, and qRT-PCR revealed minute expression in different organs and tissues with trace or no response to low temperature, drought, hormones, Ca2+, and bacterial stresses, but highly induced by A. flavus infection. It contains four exons encoding 297 aa predicted to transfer the methyl group of S-adenosyl-L-methionine (SAM). The promoter contains different cis-elements responsible for its expression characteristics. Functional characterization of AhOMT1P in transgenic Arabidopsis plants demonstrated highly inducible behavior only under A. flavus infection. The transgenic plants did not show GUS expression in any tissue(s) without inoculation of A. flavus spores. However, GUS activity increased significantly after inoculation of A. flavus and maintained a high level of expression after 48 hours of infection. These results provided a novel way for future management of peanut aflatoxins contamination through driving resistance genes in A. flavus inducible manner.